2021
DOI: 10.21037/tcr-21-700
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of SOCS4 promotes cell proliferation and migration in esophageal squamous cell carcinoma

Abstract: Background: Suppressors of cytokine signaling family member 4 (SOCS4) was shown to serve critical and multifaceted roles in the progression of numerous cancers, including hepatocellular carcinoma, thyroid cancer, breast cancer, and lung adenocarcinoma. While, the expression and the roles of SOCS4 in esophageal squamous cell carcinoma (ESCC) remain elusive. The current study is aimed to investigate the expression pattern and functions of SOCS4 in ESCC. Methods:The relationship between SOCS4 and the clinicopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…It has been shown that the SOCS family plays an important role in the regulation of cellular responses to cytokines and growth factors, and that the SOCS family is a major negative regulator of a number of signaling pathways, including JAK/STAT pathway [3,20,21] . More and more studies suggested that the SOCS family genes were the key factors in the occurrence, development, invasion and angiogenesis of malignant tumors [2,22] . However, only a limited number of studies have shown that SOCS family member are associated with HCC [23] , and the exact biological function of the SOCS family in HCC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the SOCS family plays an important role in the regulation of cellular responses to cytokines and growth factors, and that the SOCS family is a major negative regulator of a number of signaling pathways, including JAK/STAT pathway [3,20,21] . More and more studies suggested that the SOCS family genes were the key factors in the occurrence, development, invasion and angiogenesis of malignant tumors [2,22] . However, only a limited number of studies have shown that SOCS family member are associated with HCC [23] , and the exact biological function of the SOCS family in HCC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the progress achieved in the diagnosis and therapeutic regimens, the 5-year survival rate remains poor in patients with ESCA ( 2 - 4 ). Recurrence and metastasis are the major obstacles that affect the therapeutic efficacy and clinical outcomes for patients with ESCA ( 5 ). Hence, there is an urgent need to unveil the molecular mechanisms involved in the recurrence and metastasis of ESCA, which will help to screen and identify the potential therapeutic targets and pave new ways to enhance the clinical therapeutic efficacy of ESCA treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal cancer (EC) is one of the most common malignant tumors of the upper digestive tract in the world ( 1 ). Recently, the International Agency for Research on Cancer of the World Health Organization reported that in 2020, there were 600,000 new cases of EC and 540,000 EC-related deaths worldwide, making it the 8th most common cancer, and the 6th leading cause of cancer-related deaths ( 2 , 3 ). EC is also one of the top 10 malignant tumors in China, and with 320,000 new cases and 300,000 deaths, it was the 6th most common cancer and the 4th leading cause of cancer-related deaths in 2020 in China ( 4 ).…”
Section: Introductionmentioning
confidence: 99%